Proceedings of the 6th International Conference on Vehicle Technology and Intelligent Transport Systems 2020
DOI: 10.5220/0009412204810488
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Path Prediction for Traffic Scenes using LSTMs and Mixture Density Models

Abstract: This work presents an analysis of predicting multiple future paths of moving objects in traffic scenes by leveraging Long Short-Term Memory architectures (LSTMs) and Mixture Density Networks (MDNs) in a single-shot manner. Path prediction allows estimating the future positions of objects. This is useful in important applications such as security monitoring systems, Autonomous Driver Assistance Systems and assistive technologies. Normal approaches use observed positions (tracklets) of objects in video frames to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…In previous work [1,2], only the past positions of the observed object in a scene have been used to predict its future path. However, in traffic scenarios there is a rich set of additional information available about the environment of the ego vehicle and each object in the scene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work [1,2], only the past positions of the observed object in a scene have been used to predict its future path. However, in traffic scenarios there is a rich set of additional information available about the environment of the ego vehicle and each object in the scene.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], it was shown that LSTMs can be extended to predict multiple paths by combining them with Mixture Density Models (MDMs) as a final layer. However, in this work, a single path was predicted to better analyse the impact of the contextual features.…”
mentioning
confidence: 99%